Analisis Kebutuhan Materi Pelatihan Umkm di Kota Ternate - Iswadi M. Ahmad; Faisal Y. Habsyi; Datje Renjaan (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to determine the need for MSME training materials in Ternate City. The research method used in this research is a qualitative descriptive approach. Data were obtained through surveys, field observations, interviews and Focus Group Discussions (FGD). The research subjects were 30 MSME actors. The results showed that 80% needed entrepreneurial knowledge, 90.5% needed innovative spice products, 85% said they needed business planning knowledge, and 80% needed product packaging knowledge, 95% needed nutmeg production skills knowledge, and 75% needed production knowledge. ginger